1999
DOI: 10.1515/polyeng-1999-0304
|View full text |Cite
|
Sign up to set email alerts
|

On the Flow of a Polymer Melt Passing Over a Transverse Slot

Abstract: The phenomenon of hole pressure occurs whenever a polymeric or viscoelastic liquid flows over a depression in a conduit wall. Numerical simulations undertaken for the flow of an aqueous polyacrylamide melt passing over a transverse slot arc considered here. The fluid model used for this study is a White-Metzner constitutive equation describing the non-Newtonian behavior of the melt. The results were computed by an elastic-viscous split-stress finite clement method (EVSS-FEM). a mixed finite clement method inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Numerical simulation [9,14,15] and flow birefringence [10] both showed that the major assumptions (no flow in the hole and symmetry of the stress tensor about the center-line of the hole) in the HP theory are violated even at low shear rates. However, both types of studies showed that even with secondary flow in the hole, the stresses cancelled out in the integration of the stress field along the center-line (Eq.…”
Section: Evalution Of the Hpb Equationmentioning
confidence: 99%
“…Numerical simulation [9,14,15] and flow birefringence [10] both showed that the major assumptions (no flow in the hole and symmetry of the stress tensor about the center-line of the hole) in the HP theory are violated even at low shear rates. However, both types of studies showed that even with secondary flow in the hole, the stresses cancelled out in the integration of the stress field along the center-line (Eq.…”
Section: Evalution Of the Hpb Equationmentioning
confidence: 99%
“…The analysis of the rheological characteristics of non-Newtonian fluids, such as polymer solutions, in specific tools, and the method of establishing the equation, can be used to deduce the rheological equation of a polymer solution in partial pressure tools, which is helpful for analyzing the influence of partial pressure tools on pressure drops in, and the apparent viscosity of, a polymer solution. Wu et al [16] used the White–Metzner constitutive model to describe the rheological properties of a polymer solution. A finite-element method was used to numerically solve the flow of the polymer solution through a single transverse groove, the pore pressure under different Deborah numbers was obtained, and the influence of fluid characteristic parameters and groove geometry on pore pressure was analyzed.…”
Section: Introductionmentioning
confidence: 99%